Advances in Computational Science and Engineering Second International Conference, FGCN 2008, Workshops and Symposia, Sanya, Hainan Island, China, December 13-15, 2008. Revised Selected Papers - Yang, Laurence Tianruo; Park, Jong Hyuk; Vasilakos, Thanos; Zhang, Yan; Sauveron, Damien; Wang, Xingang; Jeong, Young-Sik (Communications in Computer and Information Science, 2009)
As communication and networking (CN) become specialized and fragmented, it is easy to lose sight that many topics in CN have common threads and because of this, advances in one sub-discipline may transmit to another. The presentation of results between different sub-disciplines of CN encourages this interchange for the advan- ment of CN as a whole. Of particular interest is the hybrid approach of combining ideas from one discipline with those of another to achieve a result that is more signi- cant than the sum of the individual parts. Through this hybrid philosophy, a new or common principle can be discovered which has the propensity to propagate throu- out this multifaceted discipline. This volume comprises the selection of extended versions of papers that were p- sented in their shortened form at the 2008 International Conference on Future Gene- tion Communication and Networking (http://www. sersc. org/FGCN2008/), Inter- tional Conference on Bio-Science and Bio-Technology (http://www. sersc. org/ BSBT2008/), International Symposium on u- and e- Service, Science and Technology (http://www. sersc. org/UNESST2008/), International Symposium on Database Theory and Application (http://www. sersc. org/DTA2008/), International Symposium on Control and Automation (http://www. sersc. org/CA2008/), International Symposium on Signal Processing, Image Processing and Pattern Recognition (http://www. sersc. org/SIP2008/), International Symposium on Grid and Distributed Computing (ttp://www. sersc. org/ GDC2008/), International Symposium on Smart Home (http://www. sersc. org/SH2008/), and 2009 Advanced Science and Technology (http://www. sersc. org/AST2009/).